TREN KEPEMILIKAN GAWAI SISWA SEKOLAH DASAR DI PULAU JAWA: TINJAUAN HASIL SURVEY - Indra Suhendra; Tatat Hartati; Rahman Rahman; Lina Marlina Nur Rizkiya (Balai Besar Guru Penggerak Jawa Timur, 2023)
This study aims to investigate the trends of smartphone ownership among primary school students in Java Island. The research method used was a survey using a questionnaire as a data collection instrument. The research respondents were students from grades 1 to 6 in several schools on Java Island. The survey results showed that smartphone ownership among primary school students varied depending on their grade level. Most students in grades 1 and 2 used smartphones owned by their parents, while in grades 3 to 6, the percentage of students who owned personal smartphones increased. It was found that approximately 8.7% of grade 1 students owned personal smartphones, while in grade 6, as many as 82% owned personal smartphones. These findings indicate that the ownership of smartphones among primary school students in Java Island is increasing as students progress to higher grade levels. This may be due to changes in students' needs and interests in using technology and peer influence. Although most students still use smartphones owned by their parents, the percentage of students who own personal smartphones increases in higher grades. The results of this study can serve as a reference for those who want to develop policies or programs related to smartphone usage among primary school students. In this case, schools or parents can consider the importance of education and supervision in using smartphones for students, especially those who already have personal smartphones.AbstrakPenelitian ini bertujuan untuk menginvestigasi tren kepemilikan gawai, khususnya smartphone, di kalangan siswa Sekolah Dasar di Pulau Jawa. Metode penelitian yang digunakan adalah survei dengan menggunakan kuesioner sebagai instrumen pengumpulan data. Responden penelitian adalah siswa kelas 1 hingga 6 dari beberapa sekolah di Pulau Jawa. Hasil survei menunjukkan bahwa kepemilikan gawai di kalangan siswa SD bervariasi tergantung pada kelas mereka. Mayoritas siswa kelas 1 dan 2 menggunakan smartphone milik orang tua, sedangkan pada kelas 3 hingga 6, persentase siswa yang memiliki smartphone pribadi semakin meningkat. Ditemukan bahwa sekitar 8,7% siswa kelas 1 memiliki smartphone pribadi, sedangkan pada kelas 6, sebanyak 82% siswa memiliki smartphone pribadi. Temuan ini menunjukkan bahwa kepemilikan smartphone di kalangan siswa SD di Pulau Jawa semakin tinggi seiring dengan kenaikan kelas siswa. Hal ini mungkin disebabkan oleh perubahan kebutuhan dan minat siswa dalam menggunakan teknologi, serta pengaruh dari teman sebaya. Meskipun mayoritas siswa masih menggunakan smartphone milik orang tua, persentase siswa yang memiliki smartphone pribadi semakin tinggi pada kelas yang lebih tinggi. Dalam hal ini, pihak sekolah atau orang tua dapat mempertimbangkan pentingnya pendidikan dan pengawasan dalam penggunaan smartphone bagi siswa, terutama mereka yang sudah memiliki smartphone pribadi.